Pengembangan Multimedia Berbasis Internet pada Mata Kuliah Pengujian Las - Heri Wibowo (Department of Mechanical Engineering Education, 2019)
The purpose of the learning media development is to produce multimedia from internet sources that are feasible to be applied in Welding Inspection learning. The methods used wasR&D (research and development). The development of multimedia products was carried out by collecting videos and handbooks on the welding process and inspections on the internet. The results of the developed multimedia on welding Inspections are Powerpoint Presentation equipped with videos with learning materials content of a) welding procedures, b) heat input and welding distortion, c) destructive testing, and d) non-destructive testing. The feasibility test validated that the multimedia is feasible for the learning process. The limited test on the students shows that multimedia is acceptable for the learning process in the Welding Inspection course.Pengembangan media pembelajaran ini bertujuan untuk menghasilkan multimedia dari sumber internet yang layak diterapkan pada pembelajaran Pengujian Las. Metode yang digunakan adalah R & D (research and development). Pengembangan produk multimedia dilakukan dengan menelusuri video dan hand book tentang proses dan inspeksi pengujian las yang ada di internet. Hasil pengembangan multimedia Pengujian Las adalah berupa power point yang dilengkapi video dengan materi: a) prosedur pengelasan, b) heat input dan distorsi pengelasan, c) pengujian destruktif, d) pengujian non destruktif. Uji kelayakan multimedia menyatakan multimedia layak diterapkan untuk pembelajaran. Hasil uji terbatas mahasiswa menyatakan multimedia dapat diterima untuk pembelajaran mata kuliah Pengujian Las.